Analysis of Motivation, Environment and Knowledge of Student Entrepreneurial Interests: Analisis Motivasi, Lingkungan dan Pengetahuan Terhadap Minat Wirausaha Mahasiswa - rodiah rodiah (Perkumpulan Doktor Indonesia Maju, 2023)
This study was conducted with the aim of knowing the extent to which the influence of motivation, environment, and knowledge simultaneously and partially on student entrepreneurial interest. Data Analysis Techniques with Validity Test, Reliability Test, Correlation Analysis, Hypothesis Testing, Multiple Regression Analysis, Classical Assumption Test, Regression Analysis Multiple linear. motivation, environment, knowledge together have a positive effect on student entrepreneurial interest based on the Summary model above that the R coefficient is (0.931) and the Adjusted R Square coefficient is 0.862 which means that there is an influence of motivation, environment, knowledge of (86.2 %) and the rest (13.8%) is influenced by other variables not examined. To see whether motivation, environment, knowledge have a positive and significant effect on student entrepreneurial interest, it can be seen that the fcount value of 160.871 is greater than ftable of 2.73, namely 160.871 > 2.73 with a significance level of 0.000. Motivation, environment, and knowledge have a positive and significant effect on student entrepreneurial interest as shown in the coefficient table, the value of 3.787 is greater than 1.665 with a significant level less than alpha (0.000). then Ho is rejected and Ha is accepted.